Current and Future Salinity Intrusion in the South-Western Coastal Region of Bangladesh - Ashrafuzzaman, Md (2022)
The southwestern coastal regions of Bangladesh (SWCRB) are highly exposed to saltwater intrusions brought about through cyclones and storm surges. These salinity intrusions are contributing to soil and water salinity in the coastal areas. This study aimed to determine the impact of these salinity intrusions on the quality of water and soil in three vulnerable coastal areas. In this investigation, water and soil samples were collected and analysed for pH, electrical conductivity (EC) and other trace elements. The analysis found many of the parameters to be higher than the recommended values. The study found that in soil samples there was a significant correlation between OM and ECe dS/m, as well as K and TN; and a highly significant correlation between TN and OM. This study further examined the historical salinity data at low and high tides to determine any patterns occurring alongside storm surges and cyclones. Water salinity statistics were obtained from the three locations of the Bangladesh Water Development Board (BWDB), which neighbours the study area. A Digital Evaluation Model (DEM) predicts the salinity induced by storm gushes in the corresponding impacted zones. Lastly, the study compared projections for future storm surges at current and predicted sea levels. Potential storm gushes circumstances from 1 to 9 m can impact up to 33% of the nation and 97% of the Shyamnagar Upazila. The occurrence of cyclone-related storms will increase and make cultivation and settlement in the region difficult. The predicted sea-level rises and saltwater contamination will intensify the adverse effects of salinity.